This chatbot is a smart one! Does perceived expertise increase willingness to interact with chatbots? - Molinillo-Jiménez, Sebastián; Viglia, Giampaolo; Domínguez Gómez, Javier; Ekinci, Yuksel (My University, 2019)
The development of artificial intelligence has led many companies to introduce computer operated chatbots that provide highly personalized services. The aim of this study is to explore the effect of perceived expertise on continuance intention to use a chatbot. Specifically, we portray that perceived trust is the mechanism behind this relationship and chatbot appearance (i.e., human-like vs. robot-like) a boundary condition for the effect. The research hypotheses were experimentally tested with a pilot study (n=89). Participants accessed to a simulated online chatbot for booking hotels: 41 were randomly assigned to a human-like chatbot and 38 to a robot-like chatbot. The perceived expertise of the service agent influences - through trust - consumers’ continuance intention to use the chatbot again. However, we do not find support for the moderating effect of perceived expertise on trust. These findings have practical implications as they encourage companies to adopt the chatbot as an effective channel for the provision of certain services. In addition, they can help developers to improve the design of online interactions mediated by robots.
Keywords: Marketing; Inteligencia artificial; Chatbot; Appearance; Perceived expertise; Trust; Continuance intention to use; Personalized service; Consumer behaviour; Online services